Language Learning and Learner’s Self-identity: A Psycho-Pragmatic Study of EFL Learners in Kurdistan Region - Mahmood, Ayad Hameed; Hassan, Zana Mahmood (Sulaimani Journal for Humanities, 2025)
This paper is an extract from a PhD dissertation that tackles the probable changes in the self-identity of Kurdish learners of EFL. It is generally accepted that learning a new language, such as English, will have some influence on learners’ world views. There have been many pieces of research about the relationship between language and identity. However, applying the theory in the field of EFL learners has not been thoroughly investigated. This paper targets Kurdish EFL learners at various universities in Kurdistan who were given a questionnaire of 30 items in the form of five-scale grading. The core aim of this study, which refers to the psycho-pragmatic aspect of self-identity, is to reply to the research questions based on data collection. After collecting data from 150 respondents, the main questions about whether or not learning a new language would affect the self-identity of Kurdish EFL learners will be answered. It should be mentioned that the relationship between language learning and self-identity of EFL learners is the main focus of this paper since this point is part of a bigger project which investigates all the psychological and pragmatic aspects of selfhood, identity and language learning. After dividing the learners into three types in relation to changing, keeping and dividing their self-identity, the paper ends with some conclusions.